Новые находки древнерусского ремесла в Киеве - Сагайдак, М. А.; Сергеева, М. С.; Михайлов, П. С. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummarySagaydak S. A., Sergeyeva M. S., Mikhailov P. S. New Finds of Ancient Russian Handicraftsin KievThe paper is devoted to results of the excavations in North-Western part of Kiev Podol in 1993, where the place of 1800 square meters were investigated the object of special interest was the industrial complex situated on the territory of two neighboring yards, attributed to the beginning of XIII century. The complex consisted of bone carving workshop specialized on working of arrow tips and remnants of bronze casting workshop where the enameled crosses were made. The tracks of glass manufacture also were fixed.